The construction of a dynamic assessment model of reading ability in secondary school students' English classroom - Wang Hui (Yugoslav Journal of Operations Research)
Secondary school students' reading ability in English classroom is an important ability for secondary school students' English learning, and it is also highly valued by teachers, parents as well as students. Regarding the English proficiency test, the assessment of students' English reading ability is necessary. Based on this, this paper constructs a dynamic assessment model of secondary school students' reading ability in the English classroom, and through the evaluation results of the implementation of this model in secondary school students' English reading teaching, it can be seen that the dynamic assessment model can help students to master reading strategies, significantly improve their reading performance, and have a good effect of intermediary intervention.